Keanekaragaman Jenis Burung Diurnal Di Taman Wisata Alam Pulau Menipo, Kecamatan Amarasi Timur, Kabupaten Kupang, Provinsi Nusa Tenggara Timur - Dengga, Petrus; Purnama, Maria M. E.; Riwu Kaho, Norman P. L. B. (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2022)
This research aimed to determine the diversity of bird species found in the Menipo Natural Tourism Park in May-June 2021 using a list of types. The results of this study were 27 bird species in Menipo Island Tourism Park from 185 individuals and based on the results of analyzing the diversity of diurnal bird species in Menipo Island Tourism Park, they were in the high category indicated by the diversity score of 3.11 obtained from the Shenon-Winer formula, plant species, comfort level and natural habitat factors.